Non-parametric estimation of reciprocal coordinate subtangent for right censored dependent scheme. Issue 13 (3rd July 2019) - Sreejith, T. B.; Sunoj, S. M.; Rajesh, G.
Abstract: The concept of reciprocal coordinate subtangent (RCST) has been used as a useful tool to study the monotone behavior of a continuous density function and for characterizing probability distributions. In this paper, we propose a non-parametric estimator for RCST based on the censored dependent data. Asymptotic properties of the estimator are established under suitable regularity conditions. A simulation study is carried out to examine the performance of the estimator. The usefulness of the estimator is also examined through a real data.